2016
DOI: 10.12659/msm.897731
|View full text |Cite
|
Sign up to set email alerts
|

MiR-940 Inhibited Cell Growth and Migration in Triple-Negative Breast Cancer

Abstract: BackgroundBreast cancer is the main type of cancer in women, and triple-negative breast cancer (TNBC) is a unique subtype of breast cancer. The expression of miR-940 has been shown to play an important role in various cancers; however, the role of miR-940 in TNBC remains unknown.Material/MethodsThe expression of miR-940 in TNBC tissues or cells were tested by qRT-PCR; the expression of miR-940 in cells were overexpressed by miR-940 mimics, and suppressed by anti-miR-940. Bioinformatics algorithms from TargetSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Moreover, our results also demonstrated that the capacities of proliferation, invasion, migration, and antiapoptosis, in addition to Bcl-2 expression were promoted in the miR-940 mimic, siRNA-SFRP1, and LiCl groups, while the expression of Fas and Bax was significantly reduced when compared with the NC and blank groups; these results could be reversed by miR-940 inhibitor. miR-940 has been reported to inhibit cellular proliferation and migration in triplenegative breast cancer, 13 to enhance progression of cervical cancer by repressing p27 and PTEN 39 and to facilitate invasion and proliferation of pancreatic cancer cells by inhibiting GSK3β and SFRP1. 16 Shih et al 40 confirmed that the SFRP1 expression functioning as an antagonist of the Wnt pathway provides a purported mechanism to suppress the abnormal activation of this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results also demonstrated that the capacities of proliferation, invasion, migration, and antiapoptosis, in addition to Bcl-2 expression were promoted in the miR-940 mimic, siRNA-SFRP1, and LiCl groups, while the expression of Fas and Bax was significantly reduced when compared with the NC and blank groups; these results could be reversed by miR-940 inhibitor. miR-940 has been reported to inhibit cellular proliferation and migration in triplenegative breast cancer, 13 to enhance progression of cervical cancer by repressing p27 and PTEN 39 and to facilitate invasion and proliferation of pancreatic cancer cells by inhibiting GSK3β and SFRP1. 16 Shih et al 40 confirmed that the SFRP1 expression functioning as an antagonist of the Wnt pathway provides a purported mechanism to suppress the abnormal activation of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that miR‐490 can inhibit the growth of pancreatic tumors by targeting myD88, and can also inhibit the growth of nasopharyngeal carcinoma cells by targeting nestin . However, there are also relevant reports suggesting that microRNA‐940 (miR‐940) can promote the progression of cervical cancer via the inhibition of p27 and PTEN . In addition, even though miR‐940 can inhibit the growth of breast cancer cells by targeting ZNF24, it can promote the growth of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in many studies that miR-940 was highly expressed in normal tissues compared with tumors, and miR-940 was shown to inhibit the migratory and invasive potential of cancer cells by suppressing CXCR2 [59], MIEN1 [58], MyD88 [57], Nestin [56], and ZNF24 [54]. Moreover, the Estrogen-Related Receptor Gamma (ESRRG) was targeted by miR-940, and suppression of ESRRG inhibited hepatocellular carcinoma cell lines growth and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) comprise a series of endogenous, short single-stranded non-coding RNAs (19)(20)(21)(22)(23)(24)(25) molecules) that primarily serve as gene regulators (8). These molecules negatively regulate gene expression by directly binding to partial complimentary sites in the 3'-untranslated regions (3'-UTRs) of their target genes, resulting in mRNA degradation or inhibition of translation (9).…”
Section: Introductionmentioning
confidence: 99%
“…miR-940 has been well studied in the pathogenesis of a number of types of human cancer (18)(19)(20)(21)(22); however, the expression pattern, roles and molecular mechanisms of the regulatory actions of miR-940 in glioma remain unknown. The present study aimed to further understand the roles of miR-940 by…”
Section: Introductionmentioning
confidence: 99%